Dynamics Modeling and Analysis of a 5-DOF Parallel Manipulator Arm with Closed Loop Branch Chain - Zhang Dianfan; Zhang Xingchao; Yu Jin; Dai Shijie; Zhang Shijun (Jixie chuandong)
A double closed loop 5-DOF manipulator arm is proposed， which adds a closed loop structure on the basis of（（2-UPS）+U）PU configuration to obtain a new topology configuration 2-UPS+（（2-UPS）+U）PU. The introduction of the closed loop structure enables the mechanism to obtain a higher carrying capacity and provides a new idea for the new topology configuration. The mapping of the velocity of the branch drive，the velocity of the swing angle of the branch and the generalized velocity Vo of the moving platform is derived. The decoupling matrix between the independent variable <alternatives><mover accent="true">q˙</mover> <?fx-imagestate width="1.77800000" height="3.47133350"?> <?fx-imagestate width="1.77800000" height="3.47133350"?> </alternatives> of the mechanism and the generalized velocity Vo of the moving platform is established. The mapping between the velocity of the center of mass of the swing bar，the expansion bar and the generalized velocity Vo of the moving platform in the branch chain of the mechanism is established. Based on the principle of virtual work，the dynamics model of the mechanism is established and transformed into a dynamics model with Lagrange dynamic form. The virtual prototype model of the mechanism is established in Adams simulation software，and the correctness of the derived dynamics model is verified by simulation.